Photosynthesis in sun and shade: the surprising importance of far‐red photons. Issue 2 (16th August 2022) - Zhen, Shuyang; van Iersel, Marc W.; Bugbee, Bruce
Summary: The current definition of photosynthetically active radiation includes only photons from 400 up to 700 nm, despite evidence of the synergistic interaction between far‐red photons and shorter‐wavelength photons. The synergy between far‐red and shorter‐wavelength photons has not been studied in sunlight under natural conditions. We used a filter to remove photons above 700 nm to quantify the effects on photosynthesis in diverse species under full sun, medium light intensity and vegetation shade. Far‐red photons (701 to 750 nm) in sunlight are used efficiently for photosynthesis. This is especially important for leaves in vegetation shade, where far‐red photons can be > 50% of the total incident photons between 400 and 750 nm. Far‐red photons accounted for 24–25% of leaf gross photosynthesis ( P gross ) in a C3 and a C4 species when sunlight was filtered through a leaf, and 10–14% of leaf P gross in a tree and an understory species in deep shade. Accounting for the photosynthetic activity of far‐red photons is critical for accurate measurement and modeling of photosynthesis at single leaf, canopy and ecosystem scales. This, in turn, is crucial in understanding crop productivity, the global carbon cycle and climate change impacts on agriculture and ecosystems.